2023
DOI: 10.1186/s40001-023-01084-9
|View full text |Cite
|
Sign up to set email alerts
|

The impact of lymphovascular space invasion on survival in early stage low-grade endometrioid endometrial cancer

Abstract: Background The lymphovascular space invasion (LVSI) is suggested as a prognostic factor for endometrial cancer in many studies, but it has not yet been employed in FIGO staging system. The present study was aimed to evaluate the impact of LVSI on survival in patients with early stage endometrioid endometrial cancer. Methods This retrospective cohort was conducted on early stage endometrial cancer patients who underwent surgical staging [total abdom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Furthermore, our meta-analysis demonstrated that patients with LVSI have worse OS in both stage I EC (HR=5.19, 95%CI 3.33-8.07) and stage IA grade 1 or 2 endometrioid carcinoma patients (HR=5.52, 95%CI 2.16-14.09) compared to patients without LVSI. Our research findings are in concordance with previous studies reporting a significant association between LVSI and decreased OS ( 3 , 6 , 7 ). However, it is important to note that there have been conflicting reports regarding the impact of LVSI on prognosis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, our meta-analysis demonstrated that patients with LVSI have worse OS in both stage I EC (HR=5.19, 95%CI 3.33-8.07) and stage IA grade 1 or 2 endometrioid carcinoma patients (HR=5.52, 95%CI 2.16-14.09) compared to patients without LVSI. Our research findings are in concordance with previous studies reporting a significant association between LVSI and decreased OS ( 3 , 6 , 7 ). However, it is important to note that there have been conflicting reports regarding the impact of LVSI on prognosis.…”
Section: Discussionsupporting
confidence: 93%
“…Nine studies ( 3 , 6 9 , 11 , 12 , 14 , 21 ) involving 3,337 patients evaluated the relationship between LVSI and recurrence. The recurrence rate for patients with LVSI was 18.10% (72/398), compared to 6.16% (181/2939) for patients without LVSI in stage I EC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these, lymphovascular space invasion (LVSI) has emerged as a significant predictor of both lymph node metastasis and overall survival. A study conducted in early-stage endometrial cancer patients found that LVSI significantly and independently influenced the three-year and five-year survival rates [12]. Another study echoed these findings, emphasizing that patients with lower International Federation of Obstetrics and Gynecology (FIGO) stages but with confirmed LVSI presence may be at an increased risk of recurrence and poor overall survival [13].…”
Section: Discussionmentioning
confidence: 99%
“…However, even with early diagnosis, certain clinicopathological factors indicate high recurrence rates and poor treatment outcomes [9,10]. The serous adenocarcinoma histologic subtype of EC (SAEC) and high histological grade are common independent risk factors for EC recurrence and are associated with poor survival rates [11,12]. Traditionally, these morphological features have been key factors in assessing the risk of EC recurrence [13].…”
Section: Introductionmentioning
confidence: 99%